2015
DOI: 10.4049/jimmunol.1401494
|View full text |Cite
|
Sign up to set email alerts
|

PSTPIP2, a Protein Associated with Autoinflammatory Disease, Interacts with Inhibitory Enzymes SHIP1 and Csk

Abstract: Mutations in the adaptor protein PSTPIP2 are the cause of the autoinflammatory disease chronic multifocal osteomyelitis in mice. This disease closely resembles the human disorder chronic recurrent multifocal osteomyelitis, characterized by sterile inflammation of the bones and often associated with inflammation in other organs, such as the skin. The most critical process in the disease’s development is the enhanced production of IL-1β. This excessive IL-1β is likely produced by neutrophils. In addition, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 60 publications
1
55
1
Order By: Relevance
“…LC‐MS/MS analysis of the pull‐down fraction revealed a number of known and novel Csk binding partners (Figure 4b). In addition to SCIMP itself, Csk‐SH2 bound to proteins like SHIP1, 22 LRP‐1 23 and PLCγ, 24 all previously reported as direct binding partners of Csk. Other proteins in the list identified with high scores include small GTPases or GTPase regulators such as RasL2 and RCC2, 25 thus revealing these proteins as novel Csk targets.…”
Section: Resultsmentioning
confidence: 87%
“…LC‐MS/MS analysis of the pull‐down fraction revealed a number of known and novel Csk binding partners (Figure 4b). In addition to SCIMP itself, Csk‐SH2 bound to proteins like SHIP1, 22 LRP‐1 23 and PLCγ, 24 all previously reported as direct binding partners of Csk. Other proteins in the list identified with high scores include small GTPases or GTPase regulators such as RasL2 and RCC2, 25 thus revealing these proteins as novel Csk targets.…”
Section: Resultsmentioning
confidence: 87%
“…Phosphatidylinositol (4,5)-bisphosphate (PI(4,5)P 2 ), which is the predominant phosphoinositide at the plasma membrane (van den Bogaart and ter Beest, 2014), converts into PI(3,4,5)P 3 by the action of PI3-kinases (Greenberg and Grinstein, 2002, Gu et al., 2003, Hoppe and Swanson, 2004, Terebiznik et al., 2002). PI(3,4,5)P 3 is then dephosphorylated by SHIP1 (INPP5D) and SHIP2 (INPPL1), yielding PI(3,4)P 2 (Brooks et al., 2010, Drobek et al., 2015, Fuhler et al., 2012), which in turn is converted into PI(3)P by PI 4-phosphatases. Both SHIP1 and 2 are expressed by human monocyte-derived dendritic cells (Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…The F-bar domain of PSTPIP2 has been known to interact with phosphatidylinositol bisphosphate, whereas its C-terminal domain binds protein tyrosine phosphatases of the PEST (a domain rich in proline, glutamic acid, serine, and threonine) family (5)(6)(7). Recent studies have shown that PSTPIP2 can also interact with inhibitory enzymes CsK and SHIP1 (8). Whereas human patients with genetic mutations in the PSTPIP2 gene have not been identified, missense L98P mutation in the gene Pstpip2 in mice results in severe autoinflammatory disease of the bones that mimics CRMO in humans and thus these mice are referred to as Pstpip2 cmo mice (9)(10)(11).…”
mentioning
confidence: 99%